Penerapan Metode Problem Solving untuk Meningkatkan Kompetensi Siswa pada Materi Medan Magnetik - Suparjo, Suparjo (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2022)
The objectives of this study: (1) describe the application of problem-solving methods in an effort to improve magnetic field competence, (2) describe how much magnetic field competence can be achieved through the application of problem-solving methods. This research is a classroom action research with two cycles, each cycle includes the stages of planning, action, observation, and reflection. The research subjects were 35 students of SMA Negeri 1 Sukoharjo class XII-IPA2 Semester 1 of the 2019/2020 academic year, as the object of research on magnetic field competencies, including social attitudes, knowledge, and skills competencies. The technique of collecting data on social attitude competence uses observation techniques, knowledge competence uses a written test, and skills competence uses a portfolio. The end of the study obtained social attitude competence with good criteria in the first cycle there were 27 students (77.14%) and the second cycle there were 31 students (88.57%), and the knowledge competence in the first cycle obtained the lowest score of 62, the highest 84, and the average 74.86, there were 27 (77.14%) students completed, and at the end of the second cycle the lowest score was 65, the highest was 86, and an average of 75.83, there were 30 (85.71%) students completed, while the skill competency In the first cycle, the lowest score was 75, the highest was 90, and the average was 79.29, and in the second cycle, the lowest score was 75, the highest was 95, and the average was 81.43. So the research concludes that the application of problem-solving improves competence (social attitudes, knowledge, and skills) in magnetic field materials.